EVALUATION OF HISTORY LEARNING PROGRAM IN SENIOR HIGH SCHOOL : CASE STUDY AT SMAN 10 BOGOR CITY, WEST JAVA, INDONESIA - Marta, Nuraeni; Situmorang, Robinson; Nomida, Diana; Sukardjo, Moch. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to evaluate the extent of the quality of history learning in high school. This study uses an Evaluation study using the CIPP Stufflebeam Model. This research was conducted at SMAN 10 Bogor City with data collection techniques using interview, observation, questionnaire and document analysis guidelines which were analyzed using triangulation. the results of this study indicate that history learning for the time being has not been very effective, due to several problems namely: evaluating the context in the implementation of the 2013 curriculum for history learning in secondary schools has not been well socialized to stakeholders, especially teachers as curriculum implementers in the field. in addition, based on input evaluation, it shows that teacher competence strongly supports the success of history learning, process evaluation shows that learning still uses knowledge transfer considering key facts and textbook thinking, while product evaluation looks at the use of the 2013 curriculum which divides history learning into historical subjects Indonesia and historical subjects do not provide maximum benefit, so repetition often occurs on some material. This concludes that in reality students who study history subjects lack understanding history as a continuation to ’real life’. Therefore, it is very much needed handling by making the problem as part of recommendations in an effort to improve teacher competency and professionalism, by optimizing the functions of supervisors and principals as guarantors of the quality of learning in the classroom, especially on historical subjects.